Equatorial plasma bubble generation/inhibition during 2015 St. Patrick's Day storm. Issue 9 (6th September 2017) - Rajesh, P. K.; Lin, Charles H.; Chen, C. H.; Lin, J. T.; Matsuo, Tomoko; Chou, M. Y.; Chen, W. H.; Chang, M. T.; You, C. F.
Abstract: All‐sky camera observations carried out over Taiwan showed intense equatorial plasma bubbles (EPBs) in 630.0 nm airglow images on consecutive nights of 13–16 March 2015 but were absent in the following night of 17 March when St. Patrick's Day magnetic storm occurred. Rate of total electron content (TEC) index by using Global Positioning System (GPS) network data also confirmed the absence of irregularities on the night 17 March. The results, however, revealed strong irregularities over Indian sector on the same night. Flux tube integrated Rayleigh‐Taylor instability growth rates computed using the prior (forecast) state of Thermosphere‐Ionosphere Electrodynamics General Circulation Model output after assimilating the GPS‐TEC measurements also agree with the observations, showing smaller values over Taiwan and larger values over India on the night of 17 March. The ionospheric response to the storm over Taiwan that resulted in the apparent inhibition of EPB is investigated in this study by using the data assimilation output. Results indicate that on the night of the magnetic storm, prereversal enhancement of zonal electric field over Taiwan was weaker when compared to that over India. Further analysis suggests that the absence of enhancement in the zonal electric field could be due to westward penetration electric field in response to rapid northward turning of interplanetary magnetic field that occurred during the dusk period over Taiwan. Key Points: Absence of plasma bubbles over Taiwan on St. Patricks' Day storm night despite occurring on previous four nights Data assimilation forecast indicates suppression of prereversal enhancement of eastward electric field over Taiwan Possible westward penetration electric field due to rapid northward turning of IMF Bz when Taiwan was in the dusk sector